Effects of Yi Jin Jing on enhancing muscle strength and physical performance in older individuals: a systematic review and meta-analysis - Zhang, Xiaoping; Jiang, Wenda; Chen, Zhenqi; Yang, Guang; Ren, Zhongyu (Frontiers in Medicine, 2024)
The aging population is rapidly increasing, leading to physical decline and higher risks of chronic diseases, including sarcopenia, which adversely affects muscle quality and strength. Yi Jin Jing (YJJ), a traditional Chinese exercise method, can enhance flexibility and strength, but evidence regarding its effectiveness in older adults is conflicting. This meta-analysis aims to systematically evaluate the effects of YJJ on muscle strength and physical performance in this demographic.We searched seven electronic databases: China National Knowledge Infrastructure, Wanfang Data, Sinomed, Web of Science, PubMed, Cochrane Library, and EMBASE to identify randomized controlled trials (RCTs). Following PRISMA guidelines, we quantified the effects of YJJ on muscle strength (grip strength, isokinetic strength) and physical performance (chair sit-to-stand, squatting-to-standing, shoulder flexibility, sit-and-reach tests). Treatment effects were calculated using Hedges' g. The Cochrane tool assessed risk of bias, the PEDro scale evaluated methodological quality, and the GRADE method assessed evidence quality. Data analysis was conducted using Stata 17.0 software, utilizing standardized mean differences (SMD) and 95% confidence intervals (CIs).Results:This meta-analysis included 10 RCTs involving 590 participants. The overall risk of bias was assessed to be low. The methodological quality of these studies was generally moderate, and the quality of the main results varied from low to moderate. The findings revealed that YJJ had considerable effects on the chair sit-to-stand test (Hedges'g = 1.06), squatting-to-standing test (Hedges'g = 1.08), and small to moderate effects on handgrip strength (Hedges'g = 0.25), 60°/s extensor peak torque (Hedges'g = 0.47), 60°/s extensor average power (Hedges'g = 0.31), 60°/s extensor total work (Hedges'g = 0.29), 60°/s flexor peak torque (Hedges'g = 0.42), 60°/s flexor The aging population is growing rapidly, leading to physical decline and increased risk of chronic diseases, including sarcopenia, which seriously affects muscle quality and strength. Yi Jin Jing (YJJ) is a traditional Chinese exercise method, which can enhance flexibility and strength. However, existing studies have provided conflicting evidence for the effectiveness of YJJ in the elderly.